Cointegrations amongst World Equity Market Indexes in Modern Globalization Era - Panich, Rewadee (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2019)
This study is to investigate cointegration relationships among the equity markets of seven developed countries and five developing countries and emerging economics during the transitional period to modern globalization. The study applies cointegration analyses on monthly data of equity market indexes of the above countries. Based on Johansen (1988), this study tests the validity of long-run equilibrium and applies the Error Correction Model with Vector Error Correction Model to study short-run adjustments to long-run equilibriums. The main results include that before modern globalization (1976-1990) long-run cointegrations exist between USA (DJIA), Germany (DAX), Hong Kong (HSI), Malaysia (KLS) and Japan (NKY), Korea (KS11), Thailand (SET), Taiwan (TWSE), respectively. Deviating from a long-term relationship, NKY and TWSE have shot-tern corrections to long-run equilibrium. In modern globalization (1990-2016 USA (DJIA) and Germany (DAX) each cointegrates with FTSE, HSI, JKSE, KLS, STI and TWSE. Deviating from a long-term relationship, KLS, KS11, PSE, SET and TWSE have shot-tern corrections to long-run equilibrium. Therefore, there exist long-run relationships between US and German markets and those of developing countries and emerging economies.